Peningkatan Pengetahuan Guru Bahasa Inggris SMP Kota Depok Terhadap Implementasi Asesmen Dalam Pembelajaran - Puspitasari, Maya; Juhana, Juhana; Zuhairi, Aminudin; Ardiasih, Lidwina Sri; Bachtiar, Bachtiar; Pratiwi, Widya Rizky (Universitas Muhammadiyah Malang, 2023)
Purpose – In March 2023, Master of English Education, Universitas Terbuka initiated a program of community service to improve the English teachers’ competencies This program is carried out to guide the English teachers who teach at junior high schools in Kota Depok to improve their competence and students’ achievements, as well as efforts to create a generation that has good competitiveness. Design/methodology/approach – The method used in this community service includes three stages of interrelated activities to ensure maximum achievement of results, namely: (1) needs assessment and communication regarding partners' willingness to participate in training; (2) delivering material using lecture and question and answer methods; (3) carry out practice according to the material provided. Findings – The outcome of this program is demonstrated by the improvement of teachers in creating test items, switching from questions based on text to questions of higher-order thinking skills questions. Originality/value – One element mentioned by the Supervisor of English teachers and the Head of Musyawarah Guru Mata Pelajaran (MGMP) for English subjects is the implementation of assessment. This program provides English teachers with some new knowledge, insights and perspectives about assessment in English language learning.